Defective signal transduction by the CD2 molecule in immature T-cell receptor/CD3- thymocytes. - Turka, L A (1992)
The CD2 accessory molecule mediates an activation pathway in mature T cells, transducing signals similar to those observed following stimulation of the T-cell receptor/CD3 (TCR/CD3) complex. CD2 is also one of the earliest cell surface markers to appear during thymic ontogeny and has been proposed to be a stimulatory pathway for immature thymocytes that have not yet expressed TCRs on their surface (TCR/CD3-). To examine this hypothesis highly purified TCR/CD3- human thymocytes were stimulated using mitogenic combinations of anti-CD2 monoclonal antibodies or individual biotinylated anti-CD2 monoclonal antibodies crosslinked with avidin. TCR/CD3+ thymocytes responded readily to either stimulus as determined by anti-phosphotyrosine immunoblotting, and the pattern of tyrosine phosphorylated substrates was similar to that of mature T cells. In contrast, TCR/CD3- thymocytes responded weakly and with a distinct substrate pattern. In addition, the altered signal transduced by CD2 in TCR/CD3- thymocytes did not lead to a rise in intracellular calcium, failed to induce interleukin 2 receptor expression, and did not serve as a comitogen with phorbol ester or interleukin 2, functions that were all intact in TCR/CD3+ thymocytes. Failure of TCR/CD3- thymocytes to respond to CD2 stimulation was not due to an intrinsic defect in these cells as they responded normally to phorbol ester plus calcium ionophore. In TCR/CD3- thymocytes, CD2 stimulation also failed to affect steady-state mRNA levels of the recombination-activating genes RAG1 and RAG2, whereas in TCR/CD3+ cells activation of the CD2 pathway terminated their expression. Together, these data support the concept that CD2 engagement does not deliver a stimulus to TCR/CD3- thymocytes and suggests that this molecule may not directly participate in the earliest stages of thymic development.